The Ligamentum Teres Test: A Novel and Effective Test in Diagnosing Tears of the Ligamentum Teres. (January 2014) - O'Donnell, John; Economopoulos, Kostas; Singh, Parminder; Bates, Daniel; Pritchard, Michael
Background: A ligamentum teres (LT) injury is a common finding at the time of hip arthroscopic surgery in patients with chronic groin and hip pain; however, LT tears have been difficult to identify before surgery. There have been no unique features identified on history assessment, physical examination, or imaging that reliably identify injuries of the LT preoperatively. Purpose: To report a new clinical examination to assess the presence of an LT tear: the LT test. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The study consisted of 75 patients undergoing hip arthroscopic surgery for multiple lesions. Each patient was evaluated by 2 independent examiners using the LT test, leading to a total of 150 tests being performed. The LT test is conducted with the hip flexed at 70° and 30° short of full abduction; the hip is then internally and externally rotated to its limits of motion. Pain on either internal or external rotation is consistent with a positive LT test result. Hip arthroscopic surgery was then performed and all intra-articular abnormalities noted. Arthroscopic images were taken of each LT and examined by a third independent examiner who determined the presence or absence of a tear. Clinical examination findings were compared with the arthroscopic findings to determine the sensitivity, specificity, and positive and negative predictive values. In addition, the presence of intra-articular pathological lesions was compared with the test results to determine if there was a correlation between the presence of an intra-articular pathological abnormality and a positive LT test result. Results: Of the 150 examinations performed, the test result was positive 55% of the time (77 examinations). The sensitivity and specificity of the test were 90% and 85%, respectively. The positive predictive value was 84%, and the negative predictive value was 91%. The presence of an LT tear, pincer lesion, and labral tear that required repair was associated with a positive LT test result. The κ coefficient for interobserver reliability was .80. Conclusion: The LT test is an effective way of assessing the presence of LT tears with moderate to high interobserver reliability. In addition to an LT tear, the presence of a pincer lesion or labral tear requiring repair are also associated with a positive LT test result.